Large Cell Neuroendocrine Carcinoma of the Rectum Presenting with Extensive Metastatic Disease - Vinay Minocha; Sania Shuja; Robert Ali; Emely Eid (Case Reports in Oncological Medicine)
Introduction. Rectal large cell neuroendocrine carcinoma (LCNEC) is a poorly differentiated neoplasm that is very rare and belongs within the poorest prognostic subgroup among primary colorectal neoplasms. Here, we describe a case of LCNEC of the rectum, which highlights the aggressive clinical course and poor prognosis associated with this disease. Case Presentation. We report a case of a 63-year-old male who presented to our hospital with a one-month history of lower abdominal pain, constipation, and weight loss. A computed tomography (CT) scan of the chest, abdomen, and pelvis revealed a rectal mass as well as metastatic disease of the liver and lung. Flexible sigmoidoscopy revealed a fungating, ulcerated and partially obstructing rectal mass located 6 cm from the anal verge. This mass was biopsied and pathological examination of the resected specimen revealed features consistent with a large cell neuroendocrine carcinoma. Conclusion. Rectal large cell neuroendocrine carcinomas are rare and have a significantly worse prognosis than adenocarcinomas. At diagnosis, a higher stage and metastatic disease are likely to be found. It is important to differentiate large cell, poorly differentiated neuroendocrine carcinomas from adenocarcinomas of the colon and rectum pathologically because patients may benefit from alternative cytotoxic chemotherapeutic regimens.